1983
DOI: 10.1113/jphysiol.1983.sp014539
|View full text |Cite
|
Sign up to set email alerts
|

A study of the mechanisms by which potassium moves through brain tissue in the rat.

Abstract: SUMMARY1. The flux of K+ produced by electric current across the pia-arachnoid surface of the neocortex of anaesthetized rats has been studied with K+-selective electrodes in a cup at the surface and with flame photometry.2. The potential differences developed across three regions of the rat brain (neocortex, cerebellum, hippocampus) have been measured as [K+]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
2

Year Published

1983
1983
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(84 citation statements)
references
References 31 publications
(59 reference statements)
2
80
2
Order By: Relevance
“…For many years, the primary function attributed to gap junctions in glia was their contribution to K + homeostasis during neuronal activity (34), a mechanism called K + buffering. Moreover, a modeling study has shown that the GJC between astrocytes is 5× more likely to support the K + transport than the extracellular diffusion (35). In the OG, this well-known property of K + buffering could support neuronal activity, a mechanism boosted by the K + itself via its facilitating effect on Cx30-mediated GJC between astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…For many years, the primary function attributed to gap junctions in glia was their contribution to K + homeostasis during neuronal activity (34), a mechanism called K + buffering. Moreover, a modeling study has shown that the GJC between astrocytes is 5× more likely to support the K + transport than the extracellular diffusion (35). In the OG, this well-known property of K + buffering could support neuronal activity, a mechanism boosted by the K + itself via its facilitating effect on Cx30-mediated GJC between astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…changes (dashed lines) based on a model of K+ uptake and release associated with current flow through a syncytium of cells in brain tissue (Gardner-Medwin, 1983 b). The parameters for the tissue model are the same as those employed for comparisons with other types of data elsewhere (Gardner-Medwin, 1983a), with an assumed current density at the tissue surface of 16 ,A mm-2 (see below). Each of the calculated curves for Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Another issue stems from the comparison made by Gardner-Medwin (1983a) of the observed K+ flux during current flow with the flux expected for purely extracellular transport. This comparison rests on the assumption that the brain extracellular space has approximately the normal composition attributed to it in the literature, with [K+] approximately 3 mm as in cerebrospinal fluid (Somjen, 1979).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Resolution of the extracellular potassium load following SD is primarily a function of astrocytes. 30 The astrocyte behaves as a nearly perfect potassium electrode with local changes in membrane potential difference reflective of local potassium concentration. 31 Astrocytic spatial buffering of local changes in potassium enables neuronal transmembrane potential to be re-established for subsequent discharge.…”
Section: A New Mechanismmentioning
confidence: 99%